-2x - 2y = 4
x + 5y = 10
It looks like the method it would be easiest to use to solve this system is substitution. To use substitution, let us isolate x in the second equation:
x + 5y = 10
x = -5y + 10
---
-2x - 2y = 4
-2(-5y + 10) - 2y = 4
10y - 20 - 2y = 4
8y - 20 = 4
8y = 24
y = 3
Now we can substitute back into the second equation to find x:
x + 5y = 10
x + 5(3) = 10
x + 15 = 10
x = -5
Finally, to check our work:
-2(-5) - 2(3) = 4 --> 10 - 6 = 4 <--True
-5 + 5(3) = 10 --> -5 + 15 = 10 <--True
Answer:
y = 3
x = -5